Habitat use of the endangered parasitic butterfly Phengaris arion close to its northern distribution limit. Issue 3 (16th December 2014) - Vilbas, Margus; Teder, Tiit; Tiitsaar, Anu; Kaasik, Ants; Esperk, Toomas; Leather, Simon R.; DeVries, Phil
Abstract Populations close to species distribution limits often differ in their habitat use from more central populations of the species distribution. Knowledge of species ecology derived from the latter may therefore not be sufficient to ensure successful conservation of peripheral populations. In this study, we examine habitat use of Phengaris (=Maculinea) arion (Lepidoptera, Lycaenidae), an endangered myrmecophilous butterfly, in populations close to its northern distribution limit (in Estonia). A particular emphasis is given to its interactions with other species – host plant and host ant use, and, as a novel aspect, adult predation by dragonflies. Phengaris arion was found to be restricted to grassland patches with much higher host plant abundance than shown in other regions and predicted by habitat suitability models. All direct observations of the host ant use of P. arion were limited to the colonies of Myrmica lonae, an ant species which has nowhere else been demonstrated to be the primary host of this butterfly. Our data thus contribute to the emerging understanding that host ant use in P. arion can be geographically remarkably diverse. The results indicate that dragonfly predation on adult butterflies could be an essential driver of patch occupancy in P. arion. Our findings thus suggest that top‐down influences, largely neglected in butterfly conservation, may actually need to be considered.